Sitting Position Anthropometry in Women's Reading Room of Technical Implementation Unit (UPT) Syiah Kuala University Library, Banda Aceh - nur azzah hasyyati (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Technical Implementation Unit (UPT) Syiah Kuala University Library (Unsyiah) is a State University’s library in Banda Aceh which provides a wide choice of reading rooms based on visitors' needs. One of them includes a gender-separated reading room, which is a reading room for men and a reading room for women. This difference raises the question of why the need for a separate reading room on a gender basis. Therefore, this study focuses on women's reading room located on the second floor of the Unsyiah Library. Sitting position on the floor is different from sitting on a bench where has no space restrictions between men and women. Therefore, the policies enforced by the Head of the Unsyiah Library was by creating two rooms which differentiated between genders. This application is only found in Unsyiah Banda Aceh from the basis of  Islamic Shari’a and women's privacy. Unfortunately, currently, the women’s reading room has not facilitated the needs of female student sitting positions yet. Therefore it's important to know the special anthropometry of female students study body size which includes linear dimensions, body size regions, and other aspects of student body position. The results of anthropometric studies of female student’s sitting positions are useful to prevent the wrong sitting position with the improvement of furniture's design and arranging the interior layout of the right space organization so that an appropriate reading room atmosphere can be created with academic needs. The method in this study uses the qualitative method with descriptive approach. The research aims to find out the various activities and students's seating positions in women’s reading room. Data collection techniques carried out by interview, observational data (observations and measurements) on anthropometry female students, existing rooms and the furnitures in women's reading rooms.